Analysis of Slang Words Used in Movie Script “Lady Bird”: Sociolinguistics Study - Nabila Adzra Firdausi; Hendar Hendar (Budapest International Research and Critics University, 2022)
The research entitled “Analysis of Slang Words Used in the Script of the Film “Lady Bird”: Sociolinguistic Study is concerned with the use of language in everyday life, which closely provides additional information used in the film. The purpose of this study is analyzed and examine closely the type of slang words that occur in the movie Lady Bird and the reasons behind of it. The method used in carrying out the study was a descriptive analysis method. The data used were taken from the Greta Gerwig’s movie script classify the data into their types used theory from Chapman (1988) and the reasons of the character using the slang were analysed by using theory from Allan & Burridge (2006). The results demonstrated that there are two types of slang words, namely primary slang (84%) and secondary slang (16%). Besides, there are seven reasons, namely To Address, To Form Intimate Atmosphere, To Initiate Relax Conversation, To Show Impression, To Show Intimacy, To Reveal Anger, and To Humiliate. In fact, the analysis reveal primary slang is the most used slang that emerges frequently in Lady Bird context due to the expression which commonly used in daily conversation.